PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA POKOK BAHASAN KESETIMBANGAN ION DAN pH LARUTAN GARAM KELAS XI SMA NEGERI 10 PEKANBARU - Ayu Pratiwi Sihombing; Jimmi Copriady; Erviyenni Erviyenni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research aims to determine the improvement of students ' learning achievement in the application of the Learning Discovery Learning model on the subject of ion equilibrium and pH of class salt solution XI SMA Negeri 10 Pekanbaru. This type of research is experimental research with draft research using the Randomized Control Group Pretest-Posttest Design. The population consists of 4 classes and the samples consist of 2 randomly selected classes namely the XI MIPA 1 class as the experimental class and the XI MIPA 2 class as the control class. Experiment classes are given the implementation of the Discovery Learning learning model while the control class has no Discovery learning model. Research instruments are objective questions that have been tested for validity and reliability. Research hypothesis testing using right-side test-T. Based on the results of data analysis obtained that the value of tcount = 10 > ttable = 1.67 then the hypothesis accepted this means that increasing students ' learning achievements with the application of discovery learning models are acceptable.Key Words: Discovery learning Model Learning, learning achievement, Ion equilibrium and the pH of salt solution